Proteasas de Bromeliaceae: V. Separación y purificación de sulfhidril - proteasas presentes en frutos de Bromelia balaasae Mez - Priolo de Lufrano, Nora Silvia (1988)
Almost ripe fruits of Bromelia balansae Mez (Bromeliaceae) were blade homogeneized within cold (-20 O C ) acetone, providing a crude preparation that could be partialiy solubllized in phosphate buffer (pH 6,4) containing EDTA and cysteine 5 mM. Solutions hydrolize casein (maximum a c t ~ t ypH 6.25-8.5O), the activity being enhanced by addition of cysteine. The crude enzyme was purified by molecular sieve chromatography (Sephadex G-75, Superfme) and ion exchange chromatography (DEAE- and CM-Sepharose). Three proteolitically active fractions were thus obtained